Development of a Health Guidance Support System for Lifestyle Improvement - Aoshima, T.; Tanaka, Y.; Shibata, S.; Tohyama, S.; Ohtsuka, Y.; Hattori, M.; Kashihara, H.; Nasu, S.; Usuda, T.; Sasamori, N. (Methods of Information in Medicine, 2002)
Objective: To provide automated advice for lifestyle adjustment based on an assessment of the results of a questionnaire and medical examination or health checkup data.Methods: A system was developed that gathers data based on questions regarding weight gain, exercise, smoking, sleep, eating habits, salt intake, animal fat intake, snacks, alcohol, and oral hygiene; body mass index, resting blood pressure, fasting blood sugar, total cholesterol, triglycerides, uric acid and liver function tests. Based on the relationships between the lifestyle data and the health checkup data, a health assessment sheet was generated for persons being allocated to a multiple-risk-factor syndrome group.Results: Health assessment and useful advice for lifestyle improvement were automatically extracted with the system, toward the high risk group for lifestyle related diseases. The system is operational.Conclusions: We developed a health guidance support system for lifestyle improvement. In comparison with conventional, limited advice methods, we developed a practical system that defined the necessity for lifestyle improvement more clearly, and made giving advice easier.
Keywords: Lifestyle related diseases; questionnaires; health assessment; health behavior; risk assessment; information systems